Metformin reverses mesenchymal phenotype of primary breast cancer cells through STAT3/NF-κB pathways - José Esparza-López; Juan Francisco Alvarado-Muñoz; Elizabeth Escobar-Arriaga; Alfredo Ulloa-Aguirre; María de Jesús Ibarra-Sánchez (BMC Cancer, 2019)
Abstract Background Breast cancer currently is the most frequently diagnosed neoplasm and the leading cause of death from cancer in women worldwide, which is mainly due to metastatic disease. Increasing our understanding of the molecular mechanisms leading to metastasis might thus improve the pharmacological management of the disease. Epithelial-mesenchymal transition (EMT) is a key factor that plays a major role in tumor metastasis. Some pro-inflammatory cytokines, like IL-6, have been shown to stimulate phenotypes consistent with EMT in transformed epithelial cells as well as in carcinoma cell lines. Since the EMT is one of the crucial steps for metastasis, we studied the effects of metformin (MTF) on EMT. Methods Cytotoxic effect of MTF was evaluated in eight primary breast cancer cell cultures by crystal violet assay. EMT markers and downstream signaling molecules were measured by Western blot. The effect of MTF on cell proliferation and cell migration were analyzed by MTT and Boyden chamber assays respectively. Results We observed that the response of cultured breast cancer primary cells to MTF varied; mesenchymal cells were resistant to 10 mM MTF and expressed Vimentin and SNAIL, which are associated with a mesenchymal phenotype, whereas epithelial cells were sensitive to this MTF dose, and expressed E-cadherin but not mesenchymal markers. Further, exposure of mesenchymal cells to MTF down-regulated both Vimentin and SNAIL as well as cell proliferation, but not cell migration. In an in vitro IL-6-induced EMT assay, primary breast cancer cells showing an epithelial phenotype underwent EMT upon exposure to IL-6, with concomitant activation of STAT3 and NF-κB; addition of MTF to IL-6-induced EMT reversed the expression of the mesenchymal markers Vimentin and SNAIL, decreased pSTAT3 Y705 and pNF-κB S536 and increased E-cadherin. In addition, downregulation of STAT3·activation was dependent on AMPK, but not NF-κB phosphorylation. Further, MTF inhibited cell proliferation and migration stimulated by IL-6. Conclusion These results suggest that MTF inhibits IL-6-induced EMT, cell proliferation, and migration of primary breast cancer cells by preventing the activation of STAT3 and NF-κB. STAT3 inactivation occurs through AMPK, but not NF-κB.